A Variable Resistance Respiratory Mechanics Model*. Issue 1 (July 2017) - Redmond, Daniel P.; Kim, Kyeong Tae; Morton, Sophie E.; Howe, Sarah L.; Chiew, Yeong Shiong; Chase, J. Geoffrey
Abstract: In respiratory mechanics models, resistance is often given less focus than elastance or compliance, and the impact of resistance is often simplified. Respiratory system resistance is likely to have some components that change during a breath. A variable resistance model of respiratory mechanics is presented as an extension of the single compartment model which allows resistance to change linearly with pressure during inspiration. The performance of this variable resistance model is tested against a single compartment, and a two compartment model using two clinical datasets using pressure support ventilation, and volume control ventilation with a combined 29346 breaths. The variable resistance model fits clinical data slightly better than a two compartment model, and much better than a single compartment model. The identified variable part of resistance is mostly positive, with median [IQR] of 0.665 s/L [0.484 0.903] in volume control data and 0.558 s/L [0.438 0.856] in pressure support data. This indicates that resistance increases during inspiration as pressure increases. This result seems counterintuitive, as there is no obvious physiological explanation, and may be due to ventilator artefacts.